Organizational Failure in the Aftermath of Radical Institutional Change. Issue 8 (August 2016) - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter
This paper focuses on the question of the extent to which the institutional founding environment affects organizational success after a radical institutional change. We analyse firms founded in the German Democratic Republic (GDR) that experienced the fall of the Iron Curtain in 1990 and focus on how the institutional environment of their founding period influences their failure rates. Results show that organizational failure rates vary after institutional change due to differences in institutional founding conditions. This variation is influenced by the degree of (dis)similarity between the imprinted past and the present institutional context. Discussing the time-varying effect of institutional founding conditions, we contribute to a more comprehensive understanding of imprinting and organizational failure in situations of institutional change.